Visual Storytelling Communication, Brand Visibility, and Audience Engagement: How the Creative Digital Content Works - Ersal Bioldy (Jobmark: Journal of Branding and Marketing Communication, 2022)
A brand's ability to stand out today relies heavily on the effectiveness of visual storytelling communication. This storytelling is not merely an aesthetic complement but a strategic instrument for conveying brand value. This study aims to compare three cases of creative digital content to analyze how visual storytelling impacts brand visibility and audience engagement, and to identify the strengths and weaknesses of each brand's approach. The methods used were qualitative case and content analyses. The three digital content case studies were selected for their strong performance across major social media platforms. The analysis focused on visual design elements, emotional narrative structure, brand identity consistency, and audience interaction metrics. The results and discussion indicate that content that combines a narrative that resonates with the audience and a distinctive visual identity can boost organic brand visibility. The study found that the primary strength lies in visual authenticity, which builds an emotional connection and positively impacts digital word-of-mouth. Conversely, the main weakness of the analyzed approach is the risk of losing focus on the brand message when the visual execution overwhelms the informational content. Furthermore, the rhythm of visual delivery also determines audience retention on short-form platforms. This study enriches the digital marketing communications literature by demonstrating that visual storytelling acts as a catalyst in shaping brand meaning. These findings also provide strategic guidance for practitioners and content creators in designing visual campaigns that are not only aesthetically appealing but also interactive and relevant to build sustainable audience engagement amidst digital competition.